Feasibility of energy harvesting from vertical pedestrian‐induced vibrations of footbridges for smart monitoring applications - Demartino C.; Quaranta G.; Maruccio C.; Pakrashi V. (Wiley, 2021)
AbstractThe present work is meant at contributing to the innovation of the current methodologies for pedestrian bridge monitoring. Specifically, the use of vibrational energy harvesters for self‐powered wireless structural monitoring of footbridges is here advanced for the first time, and a novel sensorless strategy is also proposed to survey remotely their serviceability conditions. In this perspective, comprehensive computer‐aided numerical investigations are initially conducted to obtain statistical estimates of the electrical energy generated from a composite piezoelectric cantilever beam subjected to the vertical footbridge response under the passage of walkers. In doing so, randomness related to the pedestrians' dynamics and footbridges with different modal features are taken into account. An investigation based on experimental data is finally presented. In detail, one case study is concerned with a footbridge prone to large vibrations due to quasi pedestrian–structure resonance condition while the second one deals with a stiffer footbridge experiencing low excitation levels. Ultimately, this study indicates that energy harvesting from vertical pedestrian‐induced vibrations can be a promising strategy for footbridges monitoring, and it provides useful design guidelines in this regard.
Keywords: Energy harvesting; Footbridge; Smart monitoring